Constructivist Grounded Theory? - Barney G. Glaser (Grounded Theory Review: An International Journal)
I refer to and use as scholarly inspiration Charmaz's excellent article on constructivist grounded theory as a tool of getting to the fundamental issues on why grounded theory is not constructivist. I show that constructivist data, if it exists at all, is a very, very small part of the data that grounded theory uses.